Moderation in Higher-Order Earnings Risk? Evidence from German Cohorts - Niklas Isaak; Robin Jessen (Institute of Labor Economics (IZA), 2024)
Women born later experience greater earnings growth volatility at given ages than older cohorts. This implies a welfare loss due to increased earnings risk. However, German registry data for the years 2001-2016 reveal a moderation in higher-order earnings risk: Men and women born later face higher skewness in earnings changes, indicating fewer large decreases than increases, and lower kurtosis at younger ages, implying fewer large earnings changes. These trends point at a welfare increase and persist for 5-year earnings changes, which are more reflective of persistent changes. During the Great Recession, males' skewness dropped sharply; younger women were unaffected.
Keywords: D31; J31; E24; 330; wage risk; income dynamics; life cycle; business cycle